Is Crime Contagious? - Jeffrey R. Kling
We test the hypothesis that criminal behavior is “contagious” – or susceptible to what economists term “endogenous effects” – by examining the extent to which lower local-area crime rates decrease arrest rates among individuals. Using data from the Moving to Opportunity (MTO) randomized housing-mobility experiment, in operation since 1994 in five U.S. cities, we exploit the fact that the effect of treatment group assignment yields different types of neighborhood changes across the five demonstration sites and use treatment-site interactions to instrument for measures of post-randomization neighborhood crime rates as well as neighborhood poverty or racial segregation in analysis of individual arrest outcomes. We find no evidence that violence is contagious; neighborhood racial segregation appears to be the most important explanation for across-neighborhood variation in arrests for violent crimes. Our only evidence for contagion comes with less serious crimes. Some estimates suggest an effect for males, but these results are imprecise. We also find evidence that young males are more likely to engage in property crimes when violent crimes are relatively more prevalent within the community. These findings are consistent with a “resource swamping” model in which increases in the prevalence of more serious crimes dilutes the police resources available for deterring less serious crimes.endogenous effects, social multiplier, arrests, social experiment